Carbon Dioxide, Odorants, Heat and Visible Cues Affect Wild Mosquito Landing in Open Spaces - Zhou, Yang-Hong; Zhang, Zhong-Wei; Fu, Yu-Fan; Zhang, Gong-Chang; Yuan, Shu (Frontiers in Behavioral Neuroscience, 2018)
CO2 and other chemicals affect mosquito blood meal seeking behaviour. Heat, humidity and black color can also serve as orientation cues. However mosquito attraction does not necessarily mean that it will land. The sequence of the cues used for mosquito landing is unclear. We performed a field study with wild mosquitoes in an open space and found that no chemicals (except pyrethrins) could completely prevent mosquitoes from landing. CO2 mimics cyclopentanone and pyridine attracted mosquitoes but did not lead to landing. No mosquito was caught in the absence of heat, although in the presence of CO2. Mosquito females commonly explore visible black objects by eyes, which is independent of infrared radiation. Humidification around the heat source may increase the detection distance but it did not affect mosquito landing. If a black object was located distant from the CO2 and heat, mosquitoes still explored the heat source. Relative to CO2 and heat, odorants, humidity and black color show lesser effects on mosquito landing.